Government Collaboration on Controlling Illegal Mining in West Nusa Tenggara Province - Gede Harimbawa; I Nyoman Sumaryadi; Djohermansyah Djohan; Deti Mulyati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Illegal mining problems arise because the Mining Business Permit (IUP) has expired, so that miners who were originally licensed because the IUP has expired are reluctant to renew them so that they become "illegal miners". The reluctance of the miners to comply with the mining administration is due to the fact that licensing management is cumbersome and time consuming and costly. Now, there are 261 Mining Business Permits (IUP) in West Nusa Tenggara, consisting of 27 metal mineral IUPs and 234 rock IUPs (West Nusa Tenggara ESDM Office, 2019). Of the 27 metal mineral IUPs, in fact there are 11 IUPs covering an area of 35,519 ha which are indicated to be in protected and conservation forest areas (Directorate General of Mineral and Coal, MEMR, 2017). In fact, based on Law number 41 of 1999 concerning Forestry, the two areas may not be used for mining activities. In this study the authors chose a qualitative research approach to uncover and discuss Government Collaboration in Controlling Illegal Miners in West Nusa Tenggara Province. This research is an "observed facts" activity that produces "knowledge based on experience". With Comte's view that only by using positive philosophy to study the human mind and social interaction can understand real social progress, the analysis of Government Collaboration in Controlling Illegal Miners in West Nusa Tenggara Province is directed to reveal the social progress of the Indonesian people in realizing prosperity and legal awareness. on society. The results of the study indicate that Government Collaboration in law enforcement for illegal miners in the jurisdiction of West Nusa Tenggara Province, is a manifestation of handling the complexities that have occurred so far. This can be resolved in various ways, one of which is the existence of a social community approach and activating the Community and/or Community Leaders, so that with this all the lowest and highest elements can unite to support the Goals, Aims and Targets that have been arranged in the RPJMD 206- 2021.